Cache memory coherence protocol for distributed systems - Aguilar Castro, José Lisandro; Sumoza Matos, Rodolfo Leonardo (Rev. Téc. Fac. Ing. Univ. Zulia)
This work proposes a protocol which man ages the coherence in the cache memory in systems with distributed memory. Cache memory is distributed in different system”™s nodes, for this reason-stored information in them must to be maintained coherent. This protocol was proved using a methodology based on the formal description using a finites states ma chine and the Spin tool.